Radar Cross Section Approach in Illusion Effects of Transformation Optics-Based Expander - Sadeghi, Mohammad Mehdi (Frontiers in Materials, 2022)
In this paper, analytical calculation has been provided to show illusion perception in electromagnetics expander. For this end, a precise analytical solution has been done for a scattered wave from expander including an object in core medium. Also, this analytical calculation has been done for a bare transformed object with different size and constitute parameters (CPs). Illusion perception, in far filed, can be illustrated using comparing the calculated scattered field patterns (SFP) of the object placed inside the expander with SFP of bare transformed object. Moreover, the same calculation and comparison has been done for nearfield SFP. In continue, for precise deduction, radar cross sections (RCSs) of both objects have been calculated and plotted using MATLAB. well functionality in illusion perception has been obtained using comparisons in both analytical SFPs parts and RCSs parts.